Time‐Resolved Bright Red to Cyan Color Tunable Mechanoluminescence from CaZnOS: Bi3+, Mn2+ for Anti‐Counterfeiting Device and Stress Sensor - Yang, Yun‐Ling; Yang, Xue‐Chun; Yuan, Jia‐Yong; Li, Ting; Fan, Yu‐Ting; Wang, Lin; Deng, Zheng; Li, Qian‐Li; Wan, Dong‐Yun; Zhao, Jing‐Tai; Zhang, Zhi‐Jun (Advanced optical materials, 2021)
Mechanoluminescence (ML) is a classical optical phenomenon that is induced by mechanical stimulus, and it can be applied to stress sensors, imaging, self‐powered display/lighting and anti‐counterfeiting. However, the realization of determining the magnitude of stress in real time by the changes of colors for stress‐induced display/lighting has been fundamentally challenging. Herein, the superior manipulation of colors from blue to red continuously by pressure or concentration is achieved in Bi,Mn co‐activated CaZnOS for the first time. CaZnOS:Bi3+,0.1% Mn2+ exhibits the ML color from red, orange, white, and cyan with the pressure from 0 to 5000 N. Moreover, ML color manipulation from cyan to red light is also achieved with difference in Mn2+ concentration. It is of note that there is a reversible phase transition of CaZnOS according to in situ X‐ray diffraction and Raman spectra at high pressure. Moreover, the correlation between crystal structure and ML properties, as well as the ML mechanism are established and discussed in detail. In conclusion, the present results demonstrate the Bi,Mn co‐activated CaZnOS as a novel ML material achieving multi‐color manipulation with great potential applications in the fields of novel mechanically stress‐induced display, ultrasound monitoring, and particularly advanced anti‐counterfeiting technology. The crystal structure of CaZnOS phosphor changes under high pressure, and the co‐doping of Bi3+ and Mn2+ ions into CaZnOS achieves the color manipulation from red to cyan with different stress.